Identification of Alkoxy Radicals as Hydrogen Atom Transfer Agents in Ce-Catalyzed C–H Functionalization - An, Qing; Xing, Yang-Yang; Pu, Ruihua; Jia, Menghui; Chen, Yuegang; Hu, Anhua; Zhang, Shuo-Qing; Yu, Na; Du, Jianbo; Zhang, Yanxia; Chen, Jinquan; Liu, Weimin; et al. (Journal of the American Chemical Society, 2023)
The intermediacy of alkoxy radicals in cerium-catalyzed C–H functionalization via H-atom abstraction has been unambiguously confirmed. Catalytically relevant Ce(IV)–alkoxide complexes have been synthesized and characterized by X-ray diffraction. Operando electron paramagnetic resonance and transient absorption spectroscopy experiments on isolated pentachloro Ce(IV) alkoxides identified alkoxy radicals as the sole heteroatom-centered radical species generated via ligand-to-metal charge transfer (LMCT) excitation. Alkoxy-radical-mediated hydrogen atom transfer (HAT) has been verified via kinetic analysis, density functional theory (DFT) calculations, and reactions under strictly chloride-free conditions. These experimental findings unambiguously establish the critical role of alkoxy radicals in Ce-LMCT catalysis and definitively preclude the involvement of chlorine radical. This study has also reinforced the necessity of a high relative ratio of alcohol vs Ce for the selective alkoxy-radical-mediated HAT, as seemingly trivial changes in the relative ratio of alcohol vs Ce can lead to drastically different mechanistic pathways. Importantly, the previously proposed chlorine radical–alcohol complex, postulated to explain alkoxy-radical-enabled selectivities in this system, has been examined under scrutiny and ruled out by regioselectivity studies, transient absorption experiments, and high-level calculations. Moreover, the peculiar selectivity of alkoxy radical generation in the LMCT homolysis of Ce(IV) heteroleptic complexes has been analyzed and back-electron transfer (BET) may have regulated the efficiency and selectivity for the formation of ligand-centered radicals.